ANALISIS KEBUTUHAN BAHAN AJAR KETERAMPILAN MENULIS BAHASA ARAB TINGKAT PEMULA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI JAKARTA - Prakasa, Fahreza; Tajuddin, Shafruddin; Setiadi, Samsi (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2024)
Bahasa adalah alat komunikasi yang paling penting dalam berinteraksi dengan siapapun di dunia ini, Bahasa tidak mungkin terpisahkan dari kehidupan manusia, karena manusialah yang menggunakan bahasa itu sendiri untuk berinteraksi. Salah satunya adalah penggunaan Bahasa didalam kegiatan Pembelajaran. Kegiatan Pembelajaran adalah suatu aktifitas yang kompleks, karena melibatkan banyak komponen, ibarat suatu aktifitas produksi/barang, bahan merupakan komponen yang akan diubah menjadi barang/produksi. Dalam menjalankan proses pembelajaran, diperlukan adanya bahan ajar yang merupakan komponen penting dalam sebuah proses belajar mengajar. Penelitian ini merupakan jenis penelitian research and development (R & D). Hasil analisis dari angket yang di distribusikan kepada mahasiswa melalui Google Form tentang analisis kebutuhan mahasiswa Program Studi Pendidikan Bahasa Arab Universitas Negeri Jakarta dapat di identifikasi bahwa mahasiswa sangat setuju dan mendukung adanya pembuatan dan pengembangan bahan ajar berbasis digital pada mata kuliah menulis Bahasa arab Tingkat pemula. Temuan dalam artikel ini secara praktis dapat ditindaklanjuti oleh penulis dan pihak Program Studi dalam mengembangkan Bahan Ajar Menulis Bahasa Arab Tingkat pemula sehingga pembelajaran menjadi bermakna, menyenangkan, dan berkelanjutan.AbstractLanguage is the most important communication tool in interacting with anyone in this world. Language cannot be separated from human life, because humans are the ones who use language themselves to interact. One of them is the use of language in learning activities. Learning activities are complex activities because they involve many components, such as a production activity/goods, materials are components that will be converted into goods/production. A teacher must have many abilities in teaching with various kinds of teaching materials. Teaching materials are very important in the learning process, especially in Arabic. Therefore, the teaching and learning process requires motivational encouragement to increase students' linguistic competence. In carrying out the learning process, teaching materials are needed which are an important component in a teaching and learning process. This research is a type of research and development (R & D) research. R & D is research that is deliberate, systematic, aimed, or directed at finding, formulating, improving, developing, producing, and testing the effectiveness of certain products, models, strategies, services, and procedures that are superior, new, effective, efficient, productive and meaningful. Based on research conducted by the author, in line with the research objective, namely to analyze the need for digital-based teaching materials. The results of the questionnaire analysis of student needs for the Arabic Language Education Study Program at Jakarta State University can be identified that students strongly agree and support the creation and development of digital-based teaching materials in beginner-level Arabic writing courses. . namely to analyze the need for digital-based teaching materials. The results of the questionnaire analysis of student needs for the Arabic Language Education Study Program at Jakarta State University can be identified that students strongly agree and support the creation and development of digital-based teaching materials in beginner-level Arabic writing courses. The findings in this article can be practically followed up by the author and the Study Program in developing beginner-level Arabic Writing Teaching Materials so that learning becomes meaningful, fun, and sustainable.